1991
DOI: 10.2116/analsci.7.19
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Methamphetamine and Amphetamine in Urine by Headspace Gas Chromatography/Mass Spectrometry

Abstract: The sensitivity of combined headspace gas chromatography (HSGC) and mass spectrometry (MS) for a stimulant (methamphetamine) and its urinary metabolite (amphetamine) was investigated. The analytical methods consisted of a combination of (1) HSGC and electron impact (EI)-MS, (2) HSGC, on-column trifluoroacetyl (TFA) derivatization of stimulants and El-MS and (3) HSGC and chemical ionization (CI)-MS using isobutane as a reagent gas. The combination of HSGC and El-MS after on-line TFA-derivatization of stimulants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…To cope with a large number of samples, we have used MBTFA as an on-column derivatization reagent, which allows the injection of an easy-to-prepare free-base ATS extract, and its instant trifluoroacetylation, without any tedious manual handling [7,8]. This derivatization method, especially in combination with the headspace technique, provides significant time savings in the GC-MS determination of ATS in urine [7,9]. Although no paper has described the use of MBTFA for the on-column derivatization of drugs in hair, Hidvegi et al [10] recently reported its use for the on-column derivatization of ATS in serum.…”
Section: Introductionmentioning
confidence: 99%
“…To cope with a large number of samples, we have used MBTFA as an on-column derivatization reagent, which allows the injection of an easy-to-prepare free-base ATS extract, and its instant trifluoroacetylation, without any tedious manual handling [7,8]. This derivatization method, especially in combination with the headspace technique, provides significant time savings in the GC-MS determination of ATS in urine [7,9]. Although no paper has described the use of MBTFA for the on-column derivatization of drugs in hair, Hidvegi et al [10] recently reported its use for the on-column derivatization of ATS in serum.…”
Section: Introductionmentioning
confidence: 99%
“…In the SIM mode, the ions at m/z 180, 194 and 208 should be selected for MDA, MDMA and MDEA, respectively. e) For the TFA-derivatization, N-methylbis(trifl uoroacetamide) (MBTFA) is also applicable as an on-column derivatization reagent [23,24]; MBTFA is injected immediately aft er the sample injection. Upon applying to a high concentration of a sample, a part of the injected analytes, however, may be underivatized.…”
Section: Notesmentioning
confidence: 99%